Diet and Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
A team of investigators at the Department of Paediatrics, Rotherham District General Hospital, and Sheffield Children's Hospital, have carried out a controlled study in 39 children to assess the effects of exclusion of dietary vasoactive amines in migraine.